PENGARUH BAURAN PEMASARAN TERHADAP VOLUME PENJUALAN AGROINDUSTRI KERIPIK NENAS DI DESA KUALU NENAS KABUPATEN KAMPAR - Nabila Audean; Novia Dewi; Roza Yulida (Indonesian Journal of Agricultural Economics, 2016)
The objective of this study was to analyzed marketing mix on agroindustrialof pineapple chips in Kualu Nenas Village based on 1) variables of marketing mix, 2) sales volume. This study used survey method with 14 pineapple chips maker as respondents which is they selected by sensus method. Data analyzed using descriptive analysis, analysis of the coefficient of determination (R2), simultaneous test (F test), partial test (t test), and multiple regressions analysis. The results of this study showed that five variables of the marketing mix, entirely in the category "Pretty Good". The affected variables of marketing mix on volume of sales is variable of product (X1) 123.21 and distribution (X5) 0.052. The author’s suggestion to the pineapple chips maker are to be able to utilize the Internet as a media campaign, maintains the certificates present on the packaging and make arrangement stall as attractive as possible.